The Research of STATCOM Based on Modular Multilevel Converter - GAO Han-ying; HU Zeng-shan; JIN Ping; YU Mei-jie (Journal of Harbin University of Science and Technology)
Capacitor voltage control and circulation current suppression are of great importance in the research of MMC topology To solve the problem of the normal half bridge MMC having no enough ability to control circulation current around threephase, we propose a novel MMC topology Each arm of the novel topology adds a H bridge to suppress circulating current, simultaneously avoid the complex coordinate transformation and decoupling control, realize the effective inhibition of the circulating current At the same time, the problem of the capacitance voltage imbalance of the submodule is solved by the capacitive voltage graded equalization control strategy and the stability of capacitors’ voltage is realizedThen, the MMC control strategy is used in high voltage and high power static synchronous compensator occasions Finally, the model of MMCSTATCOM with six halfbridge modules and one H bridge module is realized by Matlab/Simulink The simulation results demonstrate that the novel topology is effective and the control strategy is reasonable